In vivo antioxidant activity of grape, pomace and wine from three red varieties grown in Argentina: Its relationship to phenolic profile - Lingua, Mariana Soledad (2016)
The in vivo antioxidant capacity (AC) of natural antioxidants involved in the winemaking of three red grape varieties grown in Argentina and its association with the phenolic composition were studied. Polyphenols from grape, wine and pomace were capable of rescuing yeast cells from oxidative stress, probably by the induction of antioxidant enzymes, such as glutathione reductase (GR) and glutathione peroxidase (GPx). Observed AC was highly correlated with phenolic profiles, as shown by canonical correlation analysis (CCA) and multiple regression analysis (MRA). Grape samples showed the highest activity among sample types, and according to MRA kaempferol-3-glucoside and fertaric acid contributed positively, whereas ethyl gallate contributed negatively to AC of wines and pomaces.With respect to varieties, Syrah was the one with the highest activity, owing to higher contents of anthocyanins, compounds highly related to bioactivity.